Perencanaan Geometrik Dan Perkerasan Lentur Jalan Wisata Lut Atas Waq Pondok Sayur Kabupaten Bener Meriah, Aceh: Design Of Geometric And Flexible Pavement Wisata Lut Atas Road Waq Pondok Sayur Bener Meriah Regency, Aceh - Khairul Imam; Eka Mutia; Wan Alamsyah (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Jalan Wisata Lut Atas Bener Meriah Aceh is a road leading to the tourist attraction of the lake, located at 2,100 meters above sea level. The lake called Lut Atas located in Bener Meriah, Aceh, exactly in Waq Pondok Sayur Village, Bukit District. The current status of the Lut Atas Tourist Road is still in the form of a rock and gravel cover, making it difficult to access the tourist area. The purpose of this study is to calculate the throughput capacity and road age plan on the Lut Atas Tourism section, knowing the required soft pavement thickness on the Lut Atas Tourism section with the manual road design method. 2017, knows how to climb slopes and bends to ensure safety and comfort for road users. Based on the results of the 4-day LHR survey, the total number of vehicles is 125 vehicles. Calculation results of pavement thickness of Upper Lut tourist road Waq Pondok Sayur village from STA 0+000 - 3+000, with pavement thickness AC-WC 40 mm, AC-BC 60 mm, aggregate layer 400mm material (LFA) and optional 100mm backfill. The Lut Atas Tourist Trail has a geometric road plan to guide the route according to the plan of 3 bends, namely PI1 Spiral Curve (SCS), PI2 Turn Spiral Circle (SCS), Turn PI3 Spiral bend (SS). The section of Thuong Lut Tourist Road has an expected longitudinal profile of 4 vertical curves with the following details: PPV1 (vertical intersection centre) vertical convex type, PPV2 (vertical intersection centre) concave longitudinal type, PPV3 (vertical intersection centre) concave longitudinal type, PPV4 (vertical intersection centre) convex longitudinal type